A Snake Venom-Secreted Phospholipase A2 Induces Foam Cell Formation Depending on the Activation of Factors Involved in Lipid Homeostasis - Leiguez, Elbio (2018)
MT-III, a snake venom GIIA sPLA2, which shares structural and functional features with mammalian GIIA sPLA2s, activates macrophage defense functions including lipid droplet (LDs) formation, organelle involved in both lipid metabolism and inflammatory processes. Macrophages (MΦs) loaded with LDs, termed foam cells, characterize early blood vessel fatty-streak lesions during atherosclerosis. However, the factors involved in foam cell formation induced by a GIIA sPLA2 are still unknown. Here, we investigated the participation of lipid homeostasis-related factors in LD formation induced by MT-III in macrophages. We found that MT-III activated PPAR-γ and PPAR-β/δ and increased the protein levels of both transcription factors and CD36 in macrophages. Pharmacological interventions evidenced that PPAR-γ, PPAR-β/δ, and CD36 as well as the endoplasmic reticulum enzymes ACAT and DGAT are essential for LD formation. Moreover, PPAR-β/δ, but not PPAR-γ, is involved in MT-III-induced PLIN2 protein expression, and both PPAR-β/δ and PPAR-γ upregulated CD36 protein expression, which contributes to MT-III-induced COX-2 expression. Furthermore, production of 15-d-PGJ2, an activator of PPARs, induced by MT-III, was dependent on COX-1 being LDs an important platform for generation of this mediator.